Kesalahan dalam Penerjemahan Kutipan dalam Berita Bola.com - Nugraha, Anandika Panca (Kementerian Sekretariat Negara Republik Indonesia, 2020)
This article identifies and categorizes translation errors found in the translation of quotations in football stories posted on bola.com. Using functional approach, this descriptive qualitative research employs Nord’s taxonomy of translation errors as the theoretical groundwork in identifying the errors and then analyzing their functional impacts to the target quotations. After comparing the source and target translations, this research finds 13 (thirteen) errors, including pragmatic errors, text-specific errors, linguistic errors, and cultural errors. Overall, pragmatic error is found to be the most crucial type of error and most easily exposed. The findings imply that documentary translation approach in translating quotation in sport stories should not be rigidly used as this could sacrifice the expressive function that a quotation may serve. Keywords: translation errors, quotation, text function, documentary translation, sport story